Functions of stone cells and oleoresin terpenes in the conifer defense syndrome. Issue 3 (23rd October 2018) - Whitehill, Justin G. A.; Yuen, Macaire M. S.; Henderson, Hannah; Madilao, Lina; Kshatriya, Kristina; Bryan, Jennifer; Jaquish, Barry; Bohlmann, Jörg
Summary: Conifers depend on complex defense systems against herbivores. Stone cells (SC) and oleoresin are physical and chemical defenses of Sitka spruce that have been separately studied in previous work. Weevil oviposit at the tip of the previous year's apical shoot (PYAS). We investigated interactions between weevil larvae and trees in controlled oviposition experiments with resistant (R) and susceptible (S) Sitka spruce. R trees have an abundance of SC in the PYAS cortex. SC are mostly absent in S trees. R trees and S trees also differ in the composition of oleoresin terpenes. Transcriptomes of R and S trees revealed differences in long‐term weevil‐induced responses. Performance of larvae was significantly reduced on R trees compared with S trees under experimental conditions that mimicked natural oviposition behavior at apical shoot tips and may be attributed to the effects of SC. In oviposition experiments designed for larvae to feed below the area of highest SC abundance, larvae showed an unusual feeding behavior and oleoresin appeared to function as the major defense. The results support a role for both SC and oleoresin terpenes and possible synergies between these traits in the defense syndrome of weevil‐resistant Sitka spruce.